Analisis Tindak Tutur Ilokusi Dosen dalam Pembelajaran Di Universitas PGRI Wiranegara - Ruwandani, Ratih Ayu (Jurnal Simki Pedagogia, 2021)
Speech acts in learning on campus is one form of communication that realizes the achievement of learning objectives. Communication between lecturers and students, not only issuing an utterance, but there is an intention or action in the speech delivered. This study aims to describe the types, functions, characteristics of illocutionary speech acts in the speech of lecturers in the learning process at PGRI Wiranegara University. The research method used is descriptive qualitative method. The data collection technique used the recording technique and the note-taking technique. The data analysis technique was carried out by means of data reduction, data presentation, and conclusion drawing. Based on the results of this study, it shows that (a) the types of illocutionary speech acts used by lecturers in learning consist of five categories, namely assertive, directive, commissive, expressive, declarative based on several indicators (b) the functions of illocutionary speech acts used by lecturers of the faculty of pedagogy and psychology at PGRI Wirangera University in the learning process are competitive, convivial, collaborative and conflictive (c) Characteristics of illocutionary speech acts lecturers at the faculty of pedagogy and psychology at PGRI Wiranegara University have different percentages of illocutionary speech act findings in each department of education.